2018
DOI: 10.1186/s40478-018-0527-z
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal sphingosine kinase 2 subcellular localization is altered in Alzheimer’s disease brain

Abstract: BackgroundAlzheimer’s disease (AD) is characterized by the accumulation of β-amyloid (Aβ) peptides and hyperphosphorylated tau protein accompanied by neuronal loss. Aβ accumulation has been associated with an impaired sphingosine 1-phosphate (S1P) metabolism. S1P is generated by sphingosine kinases (SphKs), of which there are two isoenzymes SphK1 and SphK2, and degraded by the sphingosine 1-phosphate lyase (SPL). We previously reported, that both a decrease in SphK1 expression and an increase in SPL expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 52 publications
3
30
0
Order By: Relevance
“…We speculate that loss of SK2 function and S1P in AD is attributed to the altered lipid environment of endosomal membranes. This could impair SK2 recruitment to endosomes, a possibility that will be investigated in future studies, and may explain redistribution of SK2 from cytosol to nucleus in neurons of AD brains (Dominguez et al, 2018). SK2 deficiency abated hippocampal epileptiform activity in J20 mice, supporting prior research showing that this hyperexcitatory activity is A␤-dependent (Verret et al, 2012;A.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…We speculate that loss of SK2 function and S1P in AD is attributed to the altered lipid environment of endosomal membranes. This could impair SK2 recruitment to endosomes, a possibility that will be investigated in future studies, and may explain redistribution of SK2 from cytosol to nucleus in neurons of AD brains (Dominguez et al, 2018). SK2 deficiency abated hippocampal epileptiform activity in J20 mice, supporting prior research showing that this hyperexcitatory activity is A␤-dependent (Verret et al, 2012;A.…”
Section: Discussionsupporting
confidence: 73%
“…S1P loss was statistically significant at Braak stages III-IV, corresponding to a pre-AD neuropathological state (Braak and Braak, 1995). He et al (2010) showed loss of S1P in AD frontal cortex, whereas another study showed reduced cytosolic and increased nuclear SK2 in AD (Dominguez et al, 2018). We have also shown an inverse correlation between S1P levels and age in the hippocampus of cognitively normal females (Couttas et al, 2018), suggesting that loss of neuroprotective S1P may sensitize to neurodegeneration.…”
Section: Introductionmentioning
confidence: 57%
“…Several lines of evidence have suggested that there is an increase in SphK2 activity in the frontal cortex while SphK2 expression inhibition was observed in the temporal cortex and hippocampus of AD brains (Takasugi et al, 2011;Maceyka et al, 2012;Asle-Rousta et al, 2013). Dominguez et al (2018) have demonstrated the re-localization of SphK2 from the cytosol to the nucleus relative to Aβ pathology, leading to the upregulation of intranuclear S1P expression as well as a series of deleterious responses. This is following the evidence that S1P functions by indirectly modulating β-site APP cleaving enzyme-1 (β-secretase, BACE1), which is considered as the rate-limiting enzyme for amyloid-β peptide (Aβ) production (Takasugi et al, 2011;Maceyka et al, 2012).…”
Section: Crosstalk Between S1p and The Pathogenesis Of Alzheimer's DImentioning
confidence: 99%
“…Beyond, the activities of lipid phosphate phosphohydrolase 3 (LPP3), also known as phospholipid phosphatase 3 (PLPP3) or sphingosine-1-phosphate phosphohydrolase (SPP1), can convert FTY720-P into its inactive, dephosphorylated metabolites [100] and, thus, reverse the mechanism actions from Sphk2. In several studies, the dynamic regulation of sphingosine kinases and phosphatases was observed in some disease models such as Alzheimer's [101] or brain tumors [102]. To what extent the expression of these enzymes changes in MS and how this may affect the therapeutic efficacy of fingolimod remains to be determined.…”
Section: Sphingosine-1 Phosphate Signalingmentioning
confidence: 99%